The heavens are changing : nineteenth-century Protestant missions and Tsimshian Christianity - Neylan, Susan, 1966- (McGill-Queen's native and northern series, 2003)
"In The Heavens Are Changing Susan Neylan offers a fresh perspective on Aboriginal encounters with Protestant missions, exploring how the Tsimshian in nineteenth-century British Columbia took an active and important role in shaping forms of Christianity and, in turn, were shaped by them. She examines the nature of Protestant missions in their first generation on the north coast of British Columbia (1857-1901), focusing on the Aboriginal roles in Christianization. She pays special attention to the Euro-Canadian missionary perspective, the viewpoints of First Nations themselves, and particular events that illuminate the negotiation of Christian identities, such as forms of worship, naming practices, and mission housing." "While the Euro-Canadian record dominates historical missionary sources, Aboriginal writings illustrate both a genuine evangelicalism and an indigenized Christianity. Christian meanings were constantly challenged from both within and without the mission context through revivalism and group evangelism. Neylan interprets the relationship forged between Tsimshian and Euro-Canadian missionary as a dialogue, although not necessarily a mutually beneficial one. The process by which power was unequally distributed through missionization exposes the extent to which the social and cultural meanings to Tsimshian daily life were contested and negotiated in encounters with Christianity."--Jacket.